TEACHERS’ PERCEPTIONS OF THE CAUSES OF STUDENTS’ LOW ENROLMENT IN SENIOR SECONDARY SCHOOL PHYSICS IN OYO-NORTH, NIGERIA - LAWAL, MUHAMMED ABDULLAHI; MOHAMMED, RIDWAN ENUWA; AMUDA, AFEES AKANNI (Sokoto Educational Review, 2023)
Despite the significant contribution of physics to modern society, a decline in physics enrollment has been observed over the years. This study specifically investigated the reasons behind students’ low enrollment in Physics. The objectives focused on exploring the impact of teachers’ qualifications and gender on their perceptions of the causes of this low enrollment in senior school physics in Oyo-North, Nigeria. The study employed a descriptive survey research design, utilizing a self-designed questionnaire with a reliability index of 0.89. A convenient sampling technique was used to gather responses from 170 physics teachers across 172 senior secondary schools in Oyo-North. Data analysis included percentages, mean, standard deviation, and Chi-square tests. The findings identified various causes for the low enrollment, such as students' interest, insufficient physics textbooks, inadequate physics laboratories, the mathematical nature of physics, poorly equipped physics labs, and parental influence. The study found no significant difference in the perceptions between qualified and unqualified physics teachers regarding the causes of students’ low enrollment, nor was there a significant difference between male and female physics teachers. Ultimately, the study concluded that teachers’ qualifications and gender had no bearing on physics teachers’ perceptions of the causes behind students’ low physics enrollment in senior secondary schools. The recommendations included concerted efforts by educational stakeholders to enhance physics enrollment by providing adequate textbooks, well-equipped laboratories, and other resources to foster student interest and prevent the decline of physics in senior secondary schools in Oyo-North, Nigeria.